Pengembangan Sistem Smart Home IoT dengan Metode Logika Fuzzy Berbasis Wemos D1 - Tegar Alam Qushoyyi; Daffa Agung Nugroho; Miftahur Rahman; Adi Sucipto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to design a smart home system leveraging the Internet of Things (IoT) concept by utilizing the Wemos D1 microcontroller combined with fuzzy logic to improve home energy management and safety. The hardware development process involves integrating a PIR sensor for motion detection, a DHT11 sensor for measuring temperature and humidity, and actuators including relays for lighting and a solenoid lock for doors. The system is operated remotely using the Blynk platform and supports notification alerts through Telegram. Testing results confirm that the prototype is capable of controlling devices, tracking environmental data in real time, and effectively sending alerts when movement is detected. Overall, the system presents a practical, responsive, and user-friendly smart home solution that enhances user convenience and household security.